Enterprise agile transformation - Batista, F.; Pereira, L.; Lopes da Costa, R. (International Journal of Agile Systems and Management, 2023)
Implementing agile methods is currently one of the central topics for many organisations and teams focused on developing technological products. Although the benefits of these methods are widely recognised by the product and project management community, their implementation in organisations means going through a complex transformation with several changes in the way of working. There are few scientific studies that explain how an organisation can carry out this transformation, what are the barriers, the enablers and the recommendations that should be followed to increase agility level and drive an agile transformation successfully. Knowing that the adoption of agile methods generates several changes in roles, processes and organisational culture, this research aims to create the Enterprise Agile Transformation Model to serve as a guide for organisations to adopt and improve agile practices.